2018
DOI: 10.1016/s0140-6736(18)31694-5
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting life expectancy, years of life lost, and all-cause and cause-specific mortality for 250 causes of death: reference and alternative scenarios for 2016–40 for 195 countries and territories

Abstract: SummaryBackgroundUnderstanding potential trajectories in health and drivers of health is crucial to guiding long-term investments and policy implementation. Past work on forecasting has provided an incomplete landscape of future health scenarios, highlighting a need for a more robust modelling platform from which policy options and potential health trajectories can be assessed. This study provides a novel approach to modelling life expectancy, all-cause mortality and cause of death forecasts —and alternative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
1,041
0
41

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,623 publications
(1,215 citation statements)
references
References 43 publications
14
1,041
0
41
Order By: Relevance
“…Except for traditional risk factors such as aging, cigarette smoking, underweight, and diabetes, we also found that osteoporosis was an independent predictor of all-cause and malignant neoplasms caused mortality among men, and cardiovascular mortality among women, this observation was not mentioned in the Foreman’s study [19]. The association between osteoporosis and death may be mediated by osteoporotic fracture, which has become a major cause of death in the elderly population [36].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Except for traditional risk factors such as aging, cigarette smoking, underweight, and diabetes, we also found that osteoporosis was an independent predictor of all-cause and malignant neoplasms caused mortality among men, and cardiovascular mortality among women, this observation was not mentioned in the Foreman’s study [19]. The association between osteoporosis and death may be mediated by osteoporotic fracture, which has become a major cause of death in the elderly population [36].…”
Section: Discussionmentioning
confidence: 90%
“…Our findings provide important implications for public health. In a recent global study [19], Foreman and colleagues developed a new model and used data from the GBD 2016 study [1] to forecast life expectancy, all-cause mortality, and risk factors of death from 2016 to 2040. Their results showed that NCDs would account for a higher proportion of years of life lost (YLLs) by 2040 (67·3% of YLLs [95% UI 61·9–72·3] globally) than 2016.…”
Section: Discussionmentioning
confidence: 99%
“…1 Up to one in 10 adults worldwide has chronic kidney disease (CKD), which is invariably irreversible and mostly progressive. 1 Up to one in 10 adults worldwide has chronic kidney disease (CKD), which is invariably irreversible and mostly progressive.…”
Section: Introductionmentioning
confidence: 99%
“…High blood pressure (BP) is the leading risk factor for years of life lost throughout the world. 1 In the United States (US), nearly half of all adults have high BP, defined as BP >130/80 mmHg, which is a major risk factor for ischemic heart disease, stroke, heart failure, and chronic kidney disease. 2 Even more alarming is that hypertension-related mortality increased by 23% between 2000 and 2013.…”
Section: Introductionmentioning
confidence: 99%